A novel rotational inertia damper for heave motion suppression of semisubmersible platform in the shallow sea - Ma, Ruisheng; Bi, Kaiming; Hao, Hong (JOHN WILEY & SONS LTD, 2019)
Semisubmersible platforms (SSPs) have been widely used in the offshore industries for energy exploitation. SSP is vulnerable to the heave motions, and continuous heave motions may cause fatigue damage to the structural and nonstructural members or even sinking of the platform. It is therefore imperative to suppress the undesired heave motions of SSP. In the present study, a novel hydraulic rotational inertia damper (RID), which can amplify the fluid resistance of the submerged plates, is proposed on the basis of the concept of inerter to mitigate the heave motions of SSP. Analytical studies are conducted in both the frequency and time domains to investigate the control effectiveness of the proposed method. For comparison, the responses of the SSP controlled by the commonly adopted fixed heave plate (FHP) and tuned heave plate (THP) are also calculated. Analytical results show that the proposed RID system is more effective in reducing the heave motions of SSP, and it can achieve the identical control performance of the FHP and THP systems by using a much smaller plate size, thus smaller physical mass (less than 0.8% of the mass of the heave plate in this research). Furthermore, it is found that the RID system performs better in the harsher wave conditions, and its effectiveness increases with the increase of wave height. The proposed method provides an attractive alternative to effectively and economically suppress the heave motions of SSP in the shallow sea.